L-Proline functionalized dicationic framework of bifunctional mesoporous organosilica for the simultaneous removal of lead and nitrate ions - Dinker, Manish K.; Ajithkumar, Thalasseril G.; Kulkarni, Prashant S. (ACS Sustainable Chemistry & Engineering, 2017)
A novel bifunctional mesoporous organosilica, PEG-functionalized bis-prolinium chloride bridged mesoporous organosilica (BPBMO) was synthesized by reacting the precursor, PEG-functionalized bis-prolinium chloride bridged organosilane (BPRIL) with tetraethyl orthosilicate (TEOS) in the presence of surfactant. The chemical conformation of BPBMO was investigated by using Fourier transform infrared (FTIR), thermogravimentric analysis (TGA), C-13, and Si-29 cross-polarization/magic angle spinning (CP/MAS) NMR techniques. The characterization represents PEG-linked-prolinium (-N+Cl-) and carboxyl (-COOH) entities, constructing the dicationic framework through siloxane (Si-O-Si) linkages. The pore-wall distribution and the periodicity of BPBMO retained during the synthesis were examined by small-angle X-ray scattering (SAXS), Brunauer-Emmett-TellerBarrett-Joyner-Halenda (BET-BJH), and transmission electron microscopy (TEM) techniques. The results revealed BPBMO as a spherical shaped solid (50-100 nm) having mesopore channels hexagonally arranged with interparticle porosity (S-BET = 487 m(2)/g and D-BJH = 5.1 nm). The material has provided active binding sites for the simultaneous removal of NO3- and Pb2+ ions when introduced in the aqueous solutions of Pb(NO3)(2) (50 mg/L, pH 6). The removal of NO3- by ion-exchange with prolinium (-N+Cl-) entities and the electrostatic interaction of Pb2+ with carboxylate (-COO-) group were characterized by using Raman spectroscopy, ion chromatography, and X-ray photoelectron spectroscopy (XPS) technique. The maximum removal of NO3- and Pia' ions were achieved within 1 h of the adsorption reaction. The adsorption has followed the Langmuir isotherm model with the adsorption capacities (q(m)) of 23.04 and 21.92 mg/g for NO3- and Pb2+ ions, respectively. The efficiency of the adsorbent was also compared with other adsorbents. Further, the BPBMO material has depicted three consecutive adsorption/desorption cycles with negligible loss in the structural conformation.